Severe human parechovirus type 3 myocarditis and encephalitis in an adolescent with hypogammaglobulinemia. (July 2015) - Mardekian, Stacey K.; Fortuna, Danielle; Nix, Allan; Bhatti, Tricia; Wiley, Clayton A.; Flanders, Adam; Urtecho, Jacqueline; Sloane, Jennifer; Ahmad, Jowairiyya; Curtis, Mark T.
Highlights: A case of human parechovirus type 3 (HPeV3) myocarditis and encephalitis in an adolescent is reported. HPeV3 infection occurred in the setting of rituximab-related hypogammaglobulinemia. HPeV3 persistence for 2 years was associated with severe clinical consequences. Complete VP1 gene sequencing revealed five unique amino acid substitutions. Intravenous immunoglobulin therapy was followed by gradual clinical improvement. Summary: Human parechovirus (HPeV) belongs to the Picornaviridae family of RNA viruses. HPeV infections can be asymptomatic, lead to mild respiratory and/or gastrointestinal symptoms, or less frequently cause severe diseases such as sepsis, meningitis, encephalitis, and myocarditis. Severe neurological HPeV infections occur most commonly in infants and neonates. There are currently 16 recognized types of HPeV. HPeV type 3 (HPeV3) has been the predominant type associated with severe central nervous system disease in neonates and newborns since its discovery in 1999. Although HPeV-related infections have been reported in adults, symptomatic HPeV3 infections in adolescents and adults are uncommon. A case of severe HPeV3 myocarditis and encephalitis in an adolescent is described.